ENGLISH TEACHERS’ PROBLEMS IN APPLYING THE 2013 CURRICULUM - Yulia Nur Ekawati (English Review: Journal of English Education, 2017)
The 2013 curriculum is regarded as the current issue for teachers and students. This curriculum is based on the competencies concerning on implementing four aspects of spiritual, attitude, knowledge and skills in order to achieve students’ character building. This study, moreover, investigates the teachers’ problems in applying the 2013 curriculum at vocational high school in Tegal. Four English teachers are observed and interviewed to obtain data. The data is analyzed referring to four points; a) preparing lesson plan, b) applying the steps of teaching learning activities, c) preparing media, and d) making evaluation. The result shows that; a) three teachers do not prepare lesson plan before their teaching learning process, b) for all teachers, they understand the principles of scientific approach and the basic concept of 2013 curriculum (i.e. inquiry-based learning, project-based learning, discovery-learning, problem-based learning and task-based learning) but they do not apply it in their teaching, c) one teacher prepares the teaching media but the others do not prepare it, and d) all teachers get difficulties in assessing students’ attitude (behaviour).Keywords: English teachers’ problem, the 2013 curriculum